Adverse Selection in Dynamic Moral Hazard - Ma, C.-t. A. (Quarterly Journal of Economics, 1991)
This paper studies a multiperiod moral hazard problem under two assumptions: (i) contracts are subject to renegotiations; (ii) the agent's action has long-term effects. The action is also interpreted as a choice of characteristic or “type.” Renegotiation-proof contracts that implement various actions, including random ones, are characterized. Under appropriate conditions, the equilibrium involves the principal implementing a random action. Therefore, the equilibrium has standard properties of “adverse selection” models.